Repair, Evaluation, Maintenance, and Rehabilitation Research Program. Bibliography of Environmental Research Related to REMR. - Nunnally,Nelson R. (1986)
The Repair, Evaluation, Maintenanance and Rehabilitation (REMR) Program is designed to research problems associated with evaluating the condition of existing Civil Works structures and maintaining, repairing, and rehabilitating those structure. This annotated bibliography assesses the applicability to REMR activities of previous environmental research done by the US Army Corps of Engineers . Environmental reports and publications produced by the US Army Engineer Waterways Experiment Station, the Coastal Engineering Research Center, and the Cold Regions Research and Engineering Laboratory were reviewed, and those with potential applicability to REMR were included. The narrative portion of the document contains tables summarizing potential environmental consequences of REMR activities and indicating which bibliographic entries should be consulted for applicable environmental research. Although much work has been done within the last decade that has produced results applicable to REMR activities, several categories of REMR actions and associated environmental impacts have few or no references. Keywords: Dredging; Pollution; Aquatic systems, Debris removal, Environmental impacts, Waterways, Dredged material disposal.